Smart nanogels for cancer treatment from the perspective of functional groups - Yu, Jiachen; Liu, Yuting; Zhang, Yingchun; Ran, Rong; Kong, Zixiao; Zhao, Duoyi; Liu, Minda; Zhao, Wei; Cui, Yan; Hua, Yingqi; Gao, Lianbo; Zhang, Zhiyu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Cancer remains a significant health challenge, with chemotherapy being a critical treatment modality. However, traditional chemotherapy faces limitations due to non-specificity and toxicity. Nanogels, as advanced drug carriers, offer potential for targeted and controlled drug release, improving therapeutic efficacy and reducing side effects. Methods: This review summarizes the latest developments in nanogel-based chemotherapy drug delivery systems, focusing on the role of functional groups in drug loading and the design of smart hydrogels with controlled release mechanisms. We discuss the preparation methods of various nanogels based on different functional groups and their application in cancer treatment. Results: Nanogels composed of natural and synthetic polymers, such as chitosan, alginate, and polyacrylic acid, have been developed for chemotherapy drug delivery. Functional groups like carboxyl, disulfide, and hydroxyl groups play crucial roles in drug encapsulation and release. Smart hydrogels have been engineered to respond to tumor microenvironmental cues, such as pH, redox potential, temperature, and external stimuli like light and ultrasound, enabling targeted drug release. Discussion: The use of functional groups in nanogel preparation allows for the creation of multifunctional nanogels with high drug loading capacity, controllable release, and good targeting. These nanogels have shown promising results in preclinical studies, with enhanced antitumor effects and reduced systemic toxicity compared to traditional chemotherapy. Conclusion: The development of smart nanogels with functional group-mediated drug delivery and controlled release strategies represents a promising direction in cancer therapy. These systems offer the potential for improved patient outcomes by enhancing drug targeting and minimizing adverse effects. Further research is needed to optimize nanogel design, evaluate their safety and efficacy in clinical trials, and explore their potential for personalized medicine.